"Knock on the Door" – Exploration of Casualty Notification and the Long-Term Impact on Military Families in the UK. Issue 6 (18th August 2022) - McGill, Gill; Wilson-Menzfeld, Gemma; Moreland, Mary; Kiernan, Matthew Donal
Abstract: Receiving the news following death in service is widely referred to among the Armed Forces population as the "knock on the door". This research uniquely considered how casualty notification is undertaken when reporting the death of a member of the UK Armed Forces and the impact of this on the family and/or significant other. For this study, 15 individuals (spouses, parents, and children) participated in semi-structured interviews and this data was analyzed using Thematic Analysis. Many participants could not remember what they were told and could not remember who told them. In particular, misunderstanding and confusion arose about the roles and responsibilities of the notification officers as well as responsibility for informing other family members, including children. Media intrusion was also highlighted as a significant issue. Results also indicated that the long-term impact of loss affected participants in a variety of ways—from dealing with unexpected "triggers" to an accumulation of feelings of regret, uncertainty, and guilt resulting in a loss of control. The impact on physical and mental health is problematic without support to address this. Results also indicated a lack of access to psychological support for bereaved adults and for young children. The study findings illustrated key issues with the notification itself, short-term procedures and provisions, and the long-term impact. However, these were diverse, multi-faceted issues across the cohort and were not homogenous. Fundamentally, the information and support provided when delivering the notification of death needs to be re-addressed, as well as the longer-term support provided for bereaved families.